The Voice of Parents of Children With a Congenital Anomaly – A EUROlinkCAT Study - Holm, Kristina Garne; Neville, Amanda Julie; Pierini, Anna; Latos Bielenska, Anna; Jamry-Dziurla, Anna; Cavero-Carbonell, Clara; Garne, Ester; Clemensen, Jane (Frontiers in Pediatrics, 2021)
EUROlinkCAT aims to investigate the health and educational outcomes of children with congenital anomalies for the first 10 years of their lives. We also aim to facilitate the development of a more reciprocal relationship between families with children with congenital anomalies, health and social care professionals, and researchers by conducting focus groups. The aim of the focus groups and parent interviews was to investigate parental experiences of having a child with a heart defect requiring surgery, cleft lip, spina bifida or Down Syndrome and to identify their research priorities. In total, seven interviews with 12 parents and eight focus groups with 58 parents and two caregivers were conducted in four European countries. We found that parents request more positive information with a focus on quality of life and what the children can achieve rather than solely on the negative aspects and limitations of the congenital anomaly. Some parents also highlighted discrepancies between the family’s need for support and the lack of support received from the local authority. Finally, it was challenging for the parents to address specific research priorities. Future research should therefore focus on the potential of a child with a congenital anomaly.